Utilization of Solar Electrical Energy in Water Faucets Using Ping Sensors - Asraf, Andi; Haripuddin, Haripuddin; Imran, Al (Energy Insights, 2026)
This study aimed to determine the amount of electrical energy required to charge the battery to run the water pump, to determine the test results of the sink device using a ping sensor, and to determine the response of users from the school regarding the use of solar power on the sink. The research method used in this study is an experiment, which provides the most stringent hypothesis testing compared to other types of research. The results of this study are as follows: on the first and third days, when the pump was not on, the power generated to charge the battery was 39 and 61 Wh, respectively, indicating that the solar panel could charge the battery. On the second and fourth days, when the water pump filled the tank, the power generated was 37.7 Wh and 32.7 Wh, respectively, indicating that on the second day of the efficiency test, the solar panel produced maximum power compared to the fourth day of testing, which could charge the battery to turn on the water pump for 2.4 h. The ping sensor was declared successful and could work when it detected an object or hand according to the settings in the program script on the Arduino Uno, namely, the solenoid valve would be active when the distance detected by the sensor was less than 15 cm and released water within 0.1 s. The user's response from the school regarding the use of electrical energy was obtained using the questionnaire that has been given. The use of electrical energy in the sink was considered very good, with an average respondent score of > 4.2. This study is expected to be useful for schools to maintain the availability of water and the culture of handwashing.